2023
DOI: 10.1039/d2ra07707h
|View full text |Cite
|
Sign up to set email alerts
|

Green nanobiopolymers for ecological applications: a step towards a sustainable environment

Abstract: This perspective presents the role of biodegradable green nanobiopolymers in conserving the environment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 86 publications
0
4
0
Order By: Relevance
“…8,38,48 Moreover, nanotechnology plays a crucial role in various sectors due to their non-toxic, biodegradable, and compatible properties with few disadvantages, but these nano-objects are widely used as antioxidants, anti-fungal, anti-bacterial, and anti-cancerous and are dominant over other pharmaceuticals including Rubus ellipticus root derived NPs. [67][68][69][70][71] In conclusion, it has been deduced from the current results that Rubus fruticosus leaves were exploited for the rst time for the biogenic synthesis of silver nanoparticles that play a key role in inhibiting phytopathogens and improving the secondary metabolites. The current results are helpful in the formulation of natural bio-control agents with maximum antibacterial potential from this plant as compared to synthetic agents in controlling plant pathogens.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…8,38,48 Moreover, nanotechnology plays a crucial role in various sectors due to their non-toxic, biodegradable, and compatible properties with few disadvantages, but these nano-objects are widely used as antioxidants, anti-fungal, anti-bacterial, and anti-cancerous and are dominant over other pharmaceuticals including Rubus ellipticus root derived NPs. [67][68][69][70][71] In conclusion, it has been deduced from the current results that Rubus fruticosus leaves were exploited for the rst time for the biogenic synthesis of silver nanoparticles that play a key role in inhibiting phytopathogens and improving the secondary metabolites. The current results are helpful in the formulation of natural bio-control agents with maximum antibacterial potential from this plant as compared to synthetic agents in controlling plant pathogens.…”
Section: Discussionmentioning
confidence: 89%
“…Moreover, nanotechnology plays a crucial role in various sectors due to their non-toxic, biodegradable, and compatible properties with few disadvantages, but these nano-objects are widely used as antioxidants, anti-fungal, anti-bacterial, and anti-cancerous and are dominant over other pharmaceuticals including Rubus ellipticus root derived NPs. 67–71…”
Section: Discussionmentioning
confidence: 99%
“…The bioinspired component has different characteristics, namely, molecular interactions, cell properties, molecular mechanisms, and size. 34 Some research emphases the synthesis of silver nanoparticles with precise size, properties, and morphology, and methods like physical, chemical, and biological 35 are the mostly available conventional methods. The biological method was found to be a sustainable approach for the synthesis of nanosized particles.…”
Section: Biosynthesis Of Silver Nanoparticlesmentioning
confidence: 99%
“…Numerous biological approaches have been employed to create nanoparticles in clean, non-toxic, safe, biocompatible, and ecologically acceptable ways (Supplementary Figure S1) [20]. Metal ion accumulation by these organisms has been viewed as an economical, ecologically benign, and readily achievable occurrence [21][22][23]. It was observed that fast metal ion reduction produced stable NPs with a range of various shapes and sizes.…”
Section: Introductionmentioning
confidence: 99%